Pengaruh Adaptabilitas Karier dan Self-Efficacy terhadap Pengambilan Keputusan Karier pada Generasi Z di Kabupaten Tasikmalaya - Yulia; Aditia Abdurachman (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
The development of globalization that occurs simultaneously with the acceleration of digital transformation has created increasingly complex competition in the world of work, so that individuals are required to be able to adapt and make appropriate career choices. In this situation, Generation Z as a productive age group still faces problems in the form of a mismatch between educational background and field of work, including low job readiness that impacts suboptimal career decision-making. This study aims to analyze the influence of career adaptability and self-efficacy on career decision-making in the Generation Z group in the Tasikmalaya Regency area using a quantitative approach. The sample determination involved 100 respondents through the Probability Sampling technique with the application of Proportionate Stratified Random Sampling. The research data were collected using an ordinal scale questionnaire. Meanwhile, the analysis was conducted using multiple linear regression tests. The conclusions obtained from the analysis indicate that career adaptability has a positive and significant effect on career decision-making. Self-efficacy also shows a positive and significant influence on career decision-making. These findings indicate that an individual's ability to deal with change and confidence in one's abilities play an important role in shaping the quality of career decisions. This research provides practical emphasis on the importance of strengthening career adaptability and self-efficiency through education, career guidance services, soft skills training and work readiness improvement programs for Generation Z to help individuals make more appropriate and optimal career decisions.